SODIUM BENZOATE ASSIMILATION BY RHODOCOCCUS AETHERIVORANS UCM AC-602 - T.M.Nogina; O.G.Kisten; V.S.Pidgorskyi (Biotechnologia Acta)
Sodium benzoate (SB) is a widely used preservative (E211) and also serves as an active ingredient in several pharmaceuticals. Prolonged exposure to SB can disrupt aquatic ecosystems, adversely affecting aquatic organisms and potentially human health.